Isolation, characterization and source analysis of radiocaesium micro-particles in soil sample collected from vicinity of Fukushima Dai-ichi nuclear power plant. (November 2020) - Futagami, Fumiya; Soliman, Mohamed; Takamiya, Koichi; Sekimoto, Shun; Oki, Yuichi; Kubota, Takumi; Konno, Mitsuyuki; Mizuno, Satoshi; Ohtsuki, Tsutomu
Abstract: Radioactive caesium was released during the accident of Fukushima Dai-ichi nuclear power plant (FDNPP) into the surrounding environment. In the current work, radiocaesium micro-particles (CsMPs) and radiocaesium-rich soil particles were selectively separated from soil particles as well as from each other using autoradiography-based procedure. The applied separation scheme is based on water dilution followed by drying of the soil sample prior to imaging plate autoradiography. The SEM/EDS investigation of the individual CsMPs showed that these particles have a silicate glass structure and vary in shape with a diameter less than 10 μm. For the first time, a two-stage formation mechanism was suggested for a CsMP based on shape and structure heterogeneity of its two parts. Perfect spherical core might be formed in the first stage with a remarkable lower content of Al, and relatively higher concentrations of Si and K than an outer angulated structure, which might be attached to the core sphere during a late stage. The radiocaesium-rich soil particles have bigger size than CsMPs and have a plate-like structure with cleavages inside the grains, which suggest that these particles might be a weathered biotite. The average radioactivity ratio of 134 Cs/ 137 Cs (dated March 11, 2011) in the investigated particles was found to be 1.05 ± 0.01, which confirmed that the radiocaesium in CsMPs and in the contaminated soil particles has the same source of origin, which could be unite 3 of FDNPP. Highlights: Caesium micro-particles with glass-like structure released from Fukushima-Daiichi nuclear power plant. Distinct regions were noticed for the first time inside CsMPs. Multi-stage formation mechanism was suggested for CsMPs. Measurement of activity ratio of caesium isotopes. The source of caesium in soil particles and CsMPs was suggested as unite 3 of FDNPP.